Effects of the axial force eccentricity on the time-variant structural reliability of aging r.c. cross-sections subjected to chloride-induced corrosion. (1st January 2017) - Castaldo, P.; Palazzo, B.; Mariniello, A.
Highlights: Time-variant structural reliability analysis adopting the reliability index. Lifetime prediction of r.c. elements affected by corrosion-induced deterioration. Models of the deterioration process caused by chloride-induced corrosion. Monte Carlo simulations considering PDFs of mechanical and degradation parameters. Fiber-model for the non-linear response of r.c. sections by varying eccentricity. Abstract: Reinforced concrete structures are generally affected by degradation phenomena, which may include changes in strength and stiffness beyond the baseline conditions which are assumed in structural design. Some of these aging effects may cause component or system strengths to degrade over time, particularly when the concrete is exposed to an aggressive environment which may increase the risk of structural failure. For r.c. structures, due to the uncertainties in material and geometrical properties, in the magnitude and distribution of the loads, in the physical parameters which define the deterioration process, the structural safety should realistically be considered time-variant. In this context, this paper implements a computational probabilistic approach to predict the time-evolution of the mechanical and geometrical properties of a r.c. structural element (i.e., bridge pier) subjected to corrosion-induced deterioration as a consequence of the diffusive attack of chlorides in order to evaluate its service life. Adopting appropriate degradation models of the material properties, concrete and reinforcing steel, as well as assuming appropriate probability density functions related to mechanical and deterioration parameters, the proposed sectional approach is based on Monte Carlo simulations in order to evaluate time-variant axial force-bending moment resistance domains, with the aim to estimate the time-variant reliability index β for different axial force eccentricity values. Finally, an application of the proposed methodology to estimate the expected lifetime of a deteriorating r.c. bridge pier is described and discussed.